Wheel-rail rolling contact behavior induced by both rail surface irregularity and sleeper hanging defects on a high-speed railway line. (October 2021) - Yang, Fei; Wei, Zilong; Sun, Xianfu; Shen, Chen; Núñez, Alfredo
Highlights: Sleeper hanging defects are studied with a wheel-rail transient rolling contact model. Rail irregularities are an input for the analysis of wheel-rail contact behavior and rail degradation. Both rail irregularity geometry and its position affect severity of sleeper hanging. Sleeper hanging defects exacerbate the plastic deformation of the rail material. Sleeper hanging defects rarely affect the distribution of adhesion-slip states and rolling contact fatigue. Abstract: In this study, a wheel-rail transient rolling contact model capable of accounting for the nonlinear displacement-force properties of hanging sleepers is proposed. The sleeper hanging status affected by rail irregularities is an input for an analysis of the wheel-rail contact behavior and related rail degradation in terms of plastic deformation and rolling contact fatigue. The results indicate that the severity of sleeper hanging is significantly affected by the geometric characteristics and the relative position with respect to the sleepers of the rail surface irregularity. The sleeper hanging defects aggravate the wheel-rail impact and increase the wheel-rail contact force amplitude, contact patch size, pressure, and von Mises stress, thus exacerbating the plastic deformation of the rail material. It was also found that the sleeper hanging defects rarely affect the distribution of the adhesion-slip states and rolling contact fatigue. The knowledge gained can serve as guidance for evaluating the condition and conducting the maintenance of ballasted railway tracks.